Pengaruh Penerapan SOP Praktik di Laboratorium terhadap Tingkat Pengetahuan dan Perilaku Mahasiswa dalam Upaya K3 - Sarifah Sya'diyah; Agus Suwarni; Heru Subaris Kasjono (Poltekkes Kemenkes Yogyakarta, 2018)
Integrated laboratory is a facility available for laboratory work in the Polytechnic of Health ofYogyakarta. Practical works have many encountered obstacles despite the enforcement of theorder of practice has been implemented. This study was aimed to determine the effect of theapplication of Standard Operating Procedure (SOP) for practical work in laboratory on the levelof knowledge and behavior of students in the effort of occupational health and safety (OHS).The research method used was a quasi experiment with non-equivalent control group design.Non-probability sampling technique was used to select and assign the respondents for the experimental and control groups. Both groups consisted of 39 respondents. The normality of thedata were tested by using Kolmogorov-Smirnov test and then analyzed by using Wilcoxon OneSample test and Mann Whitney U test. The results show that the application of SOP of practicalwork influences the level of knowledge and behavior of students in the effort of OHS. The p-value <0,001 gained from the test for the value of knowledge and behavior means that the difference of knowledge and behavior between pre and post treatment in experiment group andcontrol group is significant. Differencial analysis between experiment and control groups obtained a p-value <0,001 meaning that the disparity between those groups is significant, as well. Toconclude, the application of SOP for laboratory practice affects the level of knowledge and behavior of students of OHS efforts.